ANALISIS HILANGNYA MEREK I AM GEPREK BENSU PADA PANGKALAN DATA KEKAYAAN INTELEKTUAL (PDKI) BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS: Analysis of the Disappearance of I Am Geprek Bensu Brand in the Intellectual Property Database under Law Number 20 of 2016 concerning Trademarks and Geographical Indications - Deva Annisa Nur Yuliana; Rakhmita Desmayanti; Bahasa Indonesia (Reformasi Hukum Trisakti, 2024)
The occurrence of disputes over the use of the "Bensu" trademark made PT Ayam Geprek Benny Sujono as the First to File holder of the "Bensu" trademark suddenly removed unilaterally by the Directorate General of Intellectual Property from the IP Database. This journal examines the regulation of the removal of registered trademarks in the case of the loss of the trademark "I Am Geprek Bensu" by the DJKI from the Database based on Law No.20/2016 Trademark Law and Geographical Indications and its impact. The results showed that the Decree of DJKI which removed the registered mark "I Am Geprek Bensu" owned by Benny Sujono from the Database through a Decree on behalf of the Minister (HKI-KI.06.07-11) caused inconsistency with the MIG Law, as well as contrary to Decision No.57/Pdt.SusMerek/2019/PN Niaga Jkt.Pst and Decision No.575/Pdt.SusHKI/Merek/2020/PN Niaga Jkt.Pst. Also, the impact of the abolition of the "I Am Geprek Bensu" trademark is very detrimental both materially and immaterially to PT. Ayam Geprek Benny Sujono with the loss of exclusive rights to the trademark and creates confusion and uncertainty in the community towards the steps taken by the Government.